Quantifier elimination by cylindrical algebraic decomposition based on regular chains. (July 2016) - Chen, Changbo; Moreno Maza, Marc
Abstract: A quantifier elimination algorithm by cylindrical algebraic decomposition based on regular chains is presented. The main idea is to refine a complex cylindrical tree until the signs of polynomials appearing in the tree are sufficient to distinguish the true and false cells. We report an implementation of our algorithm in theRegularChains library inMaple and illustrate its effectiveness by examples.